2017
DOI: 10.5194/nhess-17-115-2017
|View full text |Cite
|
Sign up to set email alerts
|

Heat waves in Africa 1981–2015, observations and reanalysis

Abstract: Abstract. The purpose of this article is to show the extreme temperature regime of heat waves across Africa over recent years . Heat waves have been quantified using the Heat Wave Magnitude Index daily (HWMId), which merges the duration and the intensity of extreme temperature events into a single numerical index. The HWMId enables a comparison between heat waves with different timing and location, and it has been applied to maximum and minimum temperature records. The time series used in this study have been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 18 publications
5
64
0
Order By: Relevance
“…Moreover, the effect of global warming under 2 • C level over the region is higher than that of 1.5 • C. This warming will most likely lead to an increase in the length and frequency of heat waves over the region (Russo et al 2016, Ceccherini et al 2017, Dosio 2017. Although the spatial patterns of projected changes in temperature are similar between seasons, the expected warming extent is greater during JJAS compared MAM and annual timescales.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the effect of global warming under 2 • C level over the region is higher than that of 1.5 • C. This warming will most likely lead to an increase in the length and frequency of heat waves over the region (Russo et al 2016, Ceccherini et al 2017, Dosio 2017. Although the spatial patterns of projected changes in temperature are similar between seasons, the expected warming extent is greater during JJAS compared MAM and annual timescales.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, hot extremes will become more common and deadly in many regions across the world (Gasparrini et al, 2017;Im et al, 2017;Lee & Kim, 2016;Mora et al, 2017) and in tropical Africa (Giorgi et al, 2014;Liu et al, 2017;Russo et al, 2014), with their frequency, duration, and magnitude depending on the underlying forcing scenario (Anderson et al, 2018;Dosio, 2017;Linares et al, 2014;Russo et al, 2016). Such hot extremes can have widespread impacts on human and natural systems, thereby challenging the adaptive capacity and resilience of local populations and activities (Ceccherini et al, 2017;Fontaine et al, 2013;Pal & Eltahir, 2016;Sultan & Gaetani, 2016;Zougmoré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the minimum temperature increases more rapidly than the maximum temperature, thus involving a reduction of the diurnal variation in temperature. The predictions of models based on greenhouse gas emissions scenarios showed that the global warming continues to increase (Ceccherini et al, 2017;Sylla et al, 2016;Giorgi et al, 2014;Boko et al, 2007). However, these temperature changes are not uniform.…”
Section: Introductionmentioning
confidence: 99%